2015
DOI: 10.1049/iet-rsn.2014.0292
|View full text |Cite
|
Sign up to set email alerts
|

Radiolocation and tracking of automatic identification system signals for maritime situational awareness

Abstract: The Automatic Identification System (AIS), a ship reporting system originally designed for collision avoidance, is becoming a cornerstone of maritime situational awareness. The recent increase of terrestrial networks and satellite constellations of receivers is providing global tracking data that enable a wide spectrum of applications beyond collision avoidance. Nevertheless, AIS suffers the lack of security measures that makes it prone to receiving positions that are unintentionally incorrect, jammed or delib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…Examples of observation‐based data include space‐based synthetic aperture radar (Vespe & Greidanus, ), radars (Sermi, Mugnai, Cuccoli, & Facheris, ) or maritime patrol aircrafts, remotely piloted aircrafts sensors, electro‐optical images (see Buck et al, ) and video (see Shafer, Harguess, and Forero, ). High frequency radars (see Horstmann, Grasso, Coffin, Gurgel, & Schlick, ; Braca, Grasso, Vespe, Maresca, & Horstmann, ), passive radar (Griffiths & Baker, ), Over the Horizon radar (Langellotti et al, ) and radiolocation of emissions (Papi et al, ) are areas of research for maritime situational awareness and anomaly detection. Information registries and databases : These sources contain information linking a ship identifier as often used for tracking systems, to details about its construction, history, management, safety, and security inspections. Such information is time unvarying or slowly changing if compared to the vessel position and motion.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of observation‐based data include space‐based synthetic aperture radar (Vespe & Greidanus, ), radars (Sermi, Mugnai, Cuccoli, & Facheris, ) or maritime patrol aircrafts, remotely piloted aircrafts sensors, electro‐optical images (see Buck et al, ) and video (see Shafer, Harguess, and Forero, ). High frequency radars (see Horstmann, Grasso, Coffin, Gurgel, & Schlick, ; Braca, Grasso, Vespe, Maresca, & Horstmann, ), passive radar (Griffiths & Baker, ), Over the Horizon radar (Langellotti et al, ) and radiolocation of emissions (Papi et al, ) are areas of research for maritime situational awareness and anomaly detection. Information registries and databases : These sources contain information linking a ship identifier as often used for tracking systems, to details about its construction, history, management, safety, and security inspections. Such information is time unvarying or slowly changing if compared to the vessel position and motion.…”
Section: Datamentioning
confidence: 99%
“…Different sensors can complement each other, as addressed by Boraz (), for overcoming AIS spoofing and coverage, radar range, lack of images that cover the entire globe, etc. Finally, time difference of arrival from multiple AIS receivers (Papi et al, ) or the signal strength at the receiver can be used to detect spoofing or on–off switching (Mazzarella et al, ; Mazzarella, Vespe, Tarchi, Aulicino, & Vollero, ).…”
Section: Challengesmentioning
confidence: 99%
“…As such, in order to tackle cyber-attacks, enterprises are benefiting from cyber situational awareness framework based on OODA (i.e., observe, orient, decide, and act) technique [3]. Automatic identification system (AIS) is also employed as the collision avoidance mechanism in the maritime situational awareness by which ships send their presence, identification, and location [21]. Deploying wide-area situational awareness (WASA) for power grids has provided valuable data that is used for monitoring, archiving, and envisioning the state of the dynamic system via connected sensors [7].…”
Section: Overview Of Situational Awarenessmentioning
confidence: 99%
“…Therefore, from another perspective, the correct detection of AIS closing and spoofing can help maritime authorities to detect illegal activities of ships in time, so that the safety of the relevant sea areas can be guaranteed. The authors of [12] demonstrated the feasibility of radiolocation of AIS emissions, which is the basis for future anti-spoofing and AIS verification applications. The AIS data spoofing mainly includes ship identity (MMSI) spoofing and position spoofing.…”
Section: Introductionmentioning
confidence: 99%